2021
DOI: 10.1108/wje-11-2020-0550
|View full text |Cite
|
Sign up to set email alerts
|

Source apportionment of SPM by positive matrix factorization and PM2.5 analysis in an urban industrial area

Abstract: Purpose The purpose of this study is to monitor suspended particulate matter (SPM), PM2.5 and source apportionment study for the identification of possible sources during the year 2018–2019 at Raipur, India. Design/methodology/approach Source apportionment study was performed using a multivariate receptor model, positive matrix factorization (PMFv5.0) with a view to identify the various possible sources of particulate matter in the area. Back-trajectory analysis was also performed using NOAA-HYSPLIT model to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 98 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…Aerosols are the mixture of solid and/or liquid atoms in the environment, which are generated by a variety of natural and anthropogenic activities, including industrial emissions, power stations, burning of biomass, automobile emissions, forest fires, refuse burning, volcanic eruptions, and marine salt sprays, among others. In 2018, 97 percent of cities in low and middle-income nations failed to fulfil WHO air quality guiding principles (www.who.int/airpollution/data/cities/en/), indicating a serious problem [2]. In light of the aforementioned consequence, numerous researchers have investigated the particulate concentration and seasonal deviation of atmospheric aerosols in the India [3 ,4], specifically in central India, and concluded that PM2.5-10 is emitted primarily due to soil particle re-suspension and PM2.5 emits majorly from anthropogenic activities [5].…”
Section: Introductionmentioning
confidence: 99%
“…Aerosols are the mixture of solid and/or liquid atoms in the environment, which are generated by a variety of natural and anthropogenic activities, including industrial emissions, power stations, burning of biomass, automobile emissions, forest fires, refuse burning, volcanic eruptions, and marine salt sprays, among others. In 2018, 97 percent of cities in low and middle-income nations failed to fulfil WHO air quality guiding principles (www.who.int/airpollution/data/cities/en/), indicating a serious problem [2]. In light of the aforementioned consequence, numerous researchers have investigated the particulate concentration and seasonal deviation of atmospheric aerosols in the India [3 ,4], specifically in central India, and concluded that PM2.5-10 is emitted primarily due to soil particle re-suspension and PM2.5 emits majorly from anthropogenic activities [5].…”
Section: Introductionmentioning
confidence: 99%